Community Participation for People with Trauma Injuries: A Study Protocol of a Crossover Randomised Controlled Trial of the Effectiveness of a Community Mobility Group Intervention (CarFreeMe TI). Issue 1 (13th February 2019) - George, Stacey; Barr, Christopher; Berndt, Angela; Crotty, Maria; Milte, Rachel; Nussio, Amy; Liddle, Jacki
Abstract : Background: Following traumatic brain and spinal cord injuries, maximising community participation leads to better physical and mental health outcomes. Objectives: To determine the effectiveness and health system resource use of a group intervention (CarFreeMe TI) on community participation in people with complex trauma injuries. Method: Randomised crossover trial of 54 participants, recruited from rehabilitation services in Adelaide, Australia. Inclusion criteria is a trauma injury, unable to return to full driving, aged over 18 years of age, adequate cognition/behavioural/communication abilities to participate in sessions and mobile. Exclusion criterion is living in setting where alternative transport is provided. Participants will be randomly assigned on a 1:1 allocation basis, to receiving Phase 1 CarFreeMe TI-group-based intervention or Phase 2 information related to transport options. Then, crossover to Phase 1 or 2 will occur. Primary outcome measure is community participation using a Global Positioning System. Secondary outcome measures include Community Mobility Self-efficacy Scale; CarFreeMe TI Transport Questionnaire, AQOL, EQ-5D-5L; Carer's Community Mobility Self-efficacy Scale and Modified Carer Strain Index for carers of participants. Outcome assessors will be blinded to group allocation. All analyses will be on an intention to treat basis with difference in community participation between the groups determined via a GLM ANOVA and the significance between groups on other measures using independent sample t -tests. It is hypothesised that the community mobility intervention (CarFreeMeTI) will result in increased community participation. Discussion: The results will provide proof of concept information on the feasibility and inform allocation of resources for people with complex trauma injuries. Trial registration: Australian and New Zealand Clinical Trials Register (ANZCTR): ACTRN12616001254482.